Hybrid metal-carbon nanostructures for energy-related applications - Herreros Lucas, C. (2017)
Recent technological advances such as the transition from non-renewable to renewable energy have been intimately related to the development of new nanostructured materials. A rational thinking is required for the development of nanomaterials with functional properties by targeting the combination of two or more nanocomponents with different properties, and preparation methodologies ensuring the utilisation of cheaper and abundant materials such as non-precious metals. Therefore, the main motivation of this work is to expand the frontiers of knowledge for the preparation of functional nanomaterials by designing hybrid carbon nanostructures suitable for energy storage applications containing a range of electrochemically active nanocomponents including molecules, nanoparticles and metal coordination polymers. The first chapter describes a general overview of the current approaches within the energy area to prepare uncoupled carbon nanostructures as well as the strategies to combine them with several active components (i.e. molecular metal clusters, nanoparticles and metal coordination polymers). Relevant concepts for this thesis such as electrochemical storage mechanisms, differences between hybrid and composite nanomaterials, synergetic effects and the distinction between ex situ and in situ synthetic approaches are discussed in the introductory chapter. For the sake of clarity, only the most relevant examples of hybrid carbon nanostructures from the literature will be highlighted and discussed. Before describing the hybridisation of carbon with molecules, nanoparticles and metal-coordination polymers, different carbon nanostructures will be analysed on their own due to their outstanding electrochemical properties. After the introductory chapter (Chapter 1), the thesis is followed by two parts: Part A and B. Part A, which is divided in two chapters (Chapter 2 and 3), gathers only carbon nanostructure investigations. In Chapter 2, a facile and solvent-free method is proposed for the development of few-layer graphene nanostructure from carbon tubular nanofibers. In Chapter 3, the synthesis of hollow carbon cages on the surface of carbon nanostructures is thoroughly investigated to elucidate their novel mechanism of formation. The preparation and electrochemical characterization of metal-carbon nanostructures by combining carbon nanostructure with a molecular metal cluster, metal oxide nanoparticles and metal coordination polymers are discussed in Part B. In Chapter 4 the extreme confinement inside hollow tubular carbon nanotubes is investigated to overcome the intrinsic low stability of molecular Mn12 cluster during the electrochemical process. In Chapter 5, the synthesis of metal oxide nanoparticles is carried out in the presence of hollow tubular carbon nanofibers (what we called “in situ synthesis”) where special attention is paid to the carbon surface functionalization. Only the metal oxide-carbon hybrids of interest produced in previous chapter are extensively characterized by electrochemical means to elucidate the effect of confinement with respect to their electrochemical stability. In Chapter 6, a correlation between the structure and chemical composition of a coordinated metal polymer and its electrochemical performance is established in order to gain a better understanding of the alkali intercalation/deintercalation process. One of the key findings in this thesis has been the encapsulation of electrochemically active species, shows promising results not only due to the electron transfer between the guest specie and the host carbon nanostructure, but also to the improvement in the stability during electrochemical cycling. In addition, it has been observed that the electrochemical performance of metal-carbon nanohybrids depends dramatically on the synthetic process that determines the interaction between the nanocomponents and, therefore, the synergetic effect. To sum up, the work developed in this thesis contributes to the area of hybrid metal-carbon nanostructures for energy-storage applications, including new synthetic protocols and strategies, novel hybrid materials with confined electrochemical components, advanced understanding on the electrochemical-structure relationships and important concepts related to durability/recyclability.